Mutations to ettA and lepA Cause Acinetobacter baumannii to Overcome Growth Defects in the [delta]Csra Strain in the Presence of Amino Acids - Wood, Jackson A (East Carolina University, 2023)
Acinetobacter baumannii is a Gram-negative bacterial pathogen which often causes nosocomial infections. A. baumannii is known for its incredible ability to survive drying and its high rates of multidrug resistance. Carbapenem resistant A. baumannii (CRAB) has even been classified as a critical priority for new drug discovery by the World Health Organization. We found that the gene csrA is essential for A. baumannii to grow within a host, and that deletion of csrA results in growth inhibition in complex media or media containing amino acids. To try and understand this growth inhibition, suppressor mutants of a csrA deletion strain where generated which regained the ability to grow on complex media. Some of these suppressor mutants contained point mutations in either of the genes lepA or ettA, which both produce proteins thought to be involved in translational regulation. We generated deletion mutants of both genes individually in wild-type and delta-csrA backgrounds to explore their roles in growth inhibition. We also recreated point mutations to both genes, identical to those seen in suppressor mutants to ensure these mutations were the cause of the rescued growth in delta-csrA. Analysis of growth for each strain was performed on lysogeny broth (LB) and chemically defined growth media (MOPS-A) with and without the addition of amino acids. Lysates of each strain were also analyzed by SDS-PAGE to compare protein expression. Long-term growth rates of wild-type and delta-ettA strains of A. baumannii were measured over 98 hours to see if EttA provided a survival advantage. Finally, EttA and the EttA point mutant (EttAE470V) were purified and ATPase activity was measured for each. We observed improved growth of the suppressor mutants and point mutants in delta-csrA on LB agar compared to delta-lepAdelta-csrA and delta-ettAdelta-csrA double mutants and observed similar results during growth in MOPS-A broth supplemented with amino acids. SDS-PAGE analysis showed different protein expression patterns for both suppressor mutants and point mutants of ettA when compared to the other strains. We observed higher CFU counts for the wild-type strain compared to [delta]ettA strain after 74 hours of incubation in LB. Finally, we found a significantly lower rate of ATP hydrolysis for EttAE470V compared to EttA. Based on these results, we concluded that the rescued growth in the suppressors is the result of a partial change in the structure of the proteins LepA and EttA that altered their function. We also found that the point mutation in ettA results in altered translation of specific proteins in A. baumannii which may be involved in the growth phenotype. Overall, these results showed that LepA and EttA are involved in growth defects observed in delta-csrA, and that EttA is important for A. baumannii survival during starvation, which may help it persist in hospitals.
Keywords: ettA; lepA; csrA; Amino Acids; Acinetobacter baumannii; Mutation; Amines; Biochemical Phenomena